2003
DOI: 10.1002/rem.10080
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the total oxidant demand for in situ chemical oxidation design

Abstract: Analytical techniques for designing of in situ chemical oxidation (ISCO)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 9 publications
1
26
0
1
Order By: Relevance
“…A critical success factor for chemical oxidation-remediation is the application of accurate amount of oxidant. It is vital not only for the most effective remediation at the lowest cost, but also for avoiding potential environmental risks associated with inappropriate use of oxidants [1,2,[5][6][7]. The rebound of contaminant concentrations after chemical oxidation-remediation has been reported in numerous research and engineering projects [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…A critical success factor for chemical oxidation-remediation is the application of accurate amount of oxidant. It is vital not only for the most effective remediation at the lowest cost, but also for avoiding potential environmental risks associated with inappropriate use of oxidants [1,2,[5][6][7]. The rebound of contaminant concentrations after chemical oxidation-remediation has been reported in numerous research and engineering projects [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the initial research on this topic attempted to treat the persistence of persulfate in a similar manner as permanganate; these studies assumed a finite persulfate demand for a given porous media and an upper limit on the amount of persulfate that will be consumed by porous media reductants (Hoag et al, 2000;Haselow et al, 2003;Dahmani et al, 2006). Using this approach for design purposes suggests that enough oxidant must be delivered to satisfy this "demand" before effective contaminant degradation can occur.…”
Section: Persulfate Decomposition Kinetics In Porous Media (Oxidant Pmentioning
confidence: 99%
“…Some have postulated that NOM acts as a finite sink for the persulfate oxidant, much like permanganate NOD, and that NOM will be highly depleted by the oxidation reaction (Hoag et al, 2000;Droste et al, 2002;Haselow et al, 2003). This hypothesis is supported by the fact that persulfate has long been used as a wet oxidation method for determining TOC in water samples, whereby persulfate is used to mineralize the TOC to carbon dioxide, which is then quantified (Aiken, 1992;Peyton, 1993;Koprivnjak et al, 1995).…”
Section: Porous Mediamentioning
confidence: 99%
“…In the context of ISCO, persulfate oxidant demand by aquifer materials has been considered in only a few published studies (e.g, Brown et al, 2004;Costanza et al, 2010;Dahmani et al, 2006;Haselow et al, 2003) but detailed studies on permanganate oxidant demand (Jones et al, 2006;Mumford Thomson, 2002;Mumford et al, 2005;Urynowicz et al, 2008) have shown that the kinetics of this process are complex, making the results highly dependent on test conditions such as oxidant concentration, exposure time, mixing regime, etc. This uncertainty regarding the characterization of natural oxidant demand (NOD) for persulfate is a major obstacle in the design of field-scale applications of activated persulfate for ISCO.…”
Section: Introductionmentioning
confidence: 99%